Transport Theory of Homogeneous Reacting Solutes - Cattani, C.; Laserra, E. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We consider the one-dimensional convection (advection)-dispersion equation of the transport theory of reacting solutes in porous media. A method is given for the best approximation of the numerical solution both in absence of interaction with the solid phase and in presence of discontinuous initial conditions. The class of solutions is determined by the multiresolution analysis of the partial differential operator, using Haar wavelets and splines, and it is compared with the Fourier solution.